Preliminary evaluation of a novel PSMA-targeting radiopharmaceutical [68Ga]Ga/[177Lu]Lu–NYM032 for theranostic use in prostate cancer. - Fu, Haitian; He, Huihui; Wang, Yanjuan; Li, Wenjin; Luo, Yihui; Chen, Liping; Mi, Yuanyuan; Sun, Chengwen; Mao, Yong; Yu, Chunjing (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: A novel theranostic radiopharmaceutical targeting prostate-specific membrane antigen (PSMA), [68Ga]Ga/[177Lu]Lu–NYM032, was developed and its diagnostic and therapeutic potential in the treatment of prostate cancer (PCa) was preliminarily evaluated. Methods: The diagnostic efficacy of the PET tracer [68Ga]Ga–NYM032 was first evaluated in PSMA-positive xenograft-bearing models (LNCaP models), followed by evaluation in 10 PCa patients using [68Ga]Ga–PSMA617 a comparator. Finally, the therapeutic potential of [177Lu]Lu–NYM032 was evaluated in LNCaP models. Results: [68Ga]Ga/[177Lu]Lu–NYM032 was well-tolerated, and no adverse events were observed in the preclinical and clinical studies. [68Ga]Ga–NYM032 demonstrated PSMA specificity and high radioactive uptake in LNCaP tumors. [68Ga]Ga–NYM032 uptake (SUVmax) did not differ from [68Ga]Ga–PSMA617 uptake in the same in situ lesions at the same p.i. time point (median 9.40 vs. 6.85, P = 0.123, n = 8). Compared with [68Ga]Ga–PSMA617 uptake, [68Ga]Ga–NYM032 uptake was significantly higher in osseous metastases (median 5.10 vs. 3.88, P < 0.001, n = 48), and higher in lymph node metastases (median 7.81 vs. 5.46, n = 2). [177Lu]Lu–NYM032 showed high aggregation in the lesions of LNCaP models and long retention times. [177Lu]Lu–NYM032 could inhibit tumor progression in LNCaP models, and its therapeutic efficiency strengthened with increasing radio-dosage (18.5–74 MBq/mouse). The tumor volume in the high radio-dosage treatment group (74 MBq/mouse) was significantly smaller than that in the blank control group at 21 days p.i. (107.14 ± 13.68 mm3 vs. 1351.86 ± 249.98 mm3, P < 0.001, n = 7). Conclusion: [68Ga]Ga/[177Lu]Lu-NYM032 has considerable potential as a novel and powerful theranostic radiopharmaceutical for PCa. Trial registration: The clinical evaluation of this study was registered at Clinicaltrial.gov (NCT06389695) on 29 Apr, 2024.